Measuring Expectations - David Kjellberg (Uppsala University, Department of Economics, 2006)
To evaluate measures of expectations I examine and compare some of the most common methods for capturing expectations: the futures method which utilizes financial market prices, the VAR forecast method, and the survey method. I study average expectations on the Federal funds rate target, and the main findings can be summarized as follows: i) the survey measure and the futures measure are highly correlated; the correlation coefficient is 0.81 which indicates that the measures capture the same phenomenon, ii) the survey measure consistently overestimates the realized changes in the interest rate, iii) the VAR forecast method shows little resemblance with the other methods.
urn:nbn:se:uu:diva-83076
Keywords: E43; E44; E47; 330; Interest rates; expectations; futures; VAR forecasts; survey data; Erwartungstheorie; Messung; Prognoseverfahren; Zins